Implementation of Transformational Leadership by Principals to Improve Teacher Motivation and Performance in The Digital Era - Susanti, Heni; Encep Syarifudin; Machdum Bachtiar; Ahmed, Mahmoud Tmsah; Anis Fauzi; Abdul Muin (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study explores the implementation of transformational leadership among principals in Islamic Senior High Schools in Indonesia within the context of the digital era. The study aims to analyze how transformational leadership influences teacher motivation and performance, to identify the leadership roles of principals, and to examine the challenges and strategies applied in digital educational transformation. Employing a qualitative descriptive multi-case study design, data were collected through interviews, observations, and document analysis from two Islamic Senior High Schools located in Serang Regency and Serang City. The findings reveal that principals successfully applied the four dimensions of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) in guiding teachers through digital adaptation. They acted as motivators, facilitators, and innovators, fostering collaboration and professional growth through digital initiatives. The integration of Islamic moral values such as amanah (trustworthiness), adl (justice), and ihsan (excellence) enriched the leadership’s ethical and spiritual foundation. Despite facing challenges such as digital inequality, limited infrastructure, and resistance to change, the principals implemented adaptive strategies, including continuous professional development, mentoring, and spiritual reinforcement. The study concludes that transformational leadership grounded in Islamic ethics and digital competence significantly enhances teacher motivation and performance, offering a sustainable framework for educational transformation in the 21st century.